Efektivitas Media Pembelajaran Berbasis Augmented Reality terhadap Pemahaman dan Minat Belajar Hardware Komputer Siswa SMK - Hidayah, Nurul; Dodiman, Dodiman; Elfianita, Nevi (Informatics Engineering Department, Dayanu Ikhsanuddin University, 2025)
The rapid development of information and communication technology requires the education sector to adopt more innovative and effective learning strategies. At the vocational high school level, learning activities related to computer hardware are still dominated by conventional methods that are less engaging and have not optimally improved students’ understanding. This study aims to design and develop an Augmented Reality (AR)–based learning medium to enhance students’ understanding and interest in computer hardware. A qualitative approach was employed through observation and literature review, supported by the MDLC development model and blacbox testing to ensure functional feasibility of the application. The effectiveness of the media was evaluated using a pretest–posttest design and statistical analysis. The results indicate a significant improvement in students’ understanding, as reflected by an N-Gain score of 89.58% (high category). These findings confirm that AR-based media is effective as an interactive learning tool to improve learning outcomes and student engagement in computer hardware materials.